2019
DOI: 10.1104/pp.19.00121
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral ARGONAUTEs Against Turnip Crinkle Virus Revealed by Image-Based Trait Analysis

Abstract: J.C.B.); 0000-0003-3572-129X (J.C.C.).RNA-based silencing functions as an important antiviral immunity mechanism in plants. Plant viruses evolved to encode viral suppressors of RNA silencing (VSRs) that interfere with the function of key components in the silencing pathway. As effectors in the RNA silencing pathway, ARGONAUTE (AGO) proteins are targeted by some VSRs, such as that encoded by Turnip crinkle virus (TCV). A VSR-deficient TCV mutant was used to identify AGO proteins with antiviral activities during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The Col-0 vs. P1/HC Tu network specifically highlighted the relationship between AGOs and viral resistance. Previous studies demonstrated that AGO2 and AGO3 upregulated to enhance the viral resistance (Alazem et al 2017 ; Harvey et al 2011 ; Zheng et al 2019 ). AGO2 is a target of miR403, which is negatively regulated by AGO1 (Harvey et al 2011 ), suggesting the upregulation of AGO2 in response to AGO1 degradation in P1/HC Tu plants.…”
Section: Discussionmentioning
confidence: 99%
“…The Col-0 vs. P1/HC Tu network specifically highlighted the relationship between AGOs and viral resistance. Previous studies demonstrated that AGO2 and AGO3 upregulated to enhance the viral resistance (Alazem et al 2017 ; Harvey et al 2011 ; Zheng et al 2019 ). AGO2 is a target of miR403, which is negatively regulated by AGO1 (Harvey et al 2011 ), suggesting the upregulation of AGO2 in response to AGO1 degradation in P1/HC Tu plants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, connections have been drawn between the endomembrane system and RNA silencing (reviewed in Kim et al, 2014). In the model plant Arabidopsis thaliana, electron microscopy unveiled an enrichment of the Argonaute protein AGO1, a central player in PTGS, in close proximity to Golgi (Derrien et al, 2012); another Argonaute protein, AGO7, which has been recently shown to play a role in anti-viral defence (Zheng et al, 2019), also co-purifies with membranes and concentrates in cytoplasmic bodies linked to the ER/Golgi endomembrane system (Jouannet et al, 2012). It seems therefore plausible that this subcellular localization is permissive for a direct targeting of RNA silencing, although further experiments will be necessary to uncover the exact molecular mechanism underlying this activity of V3.…”
Section: Discussionmentioning
confidence: 99%
“…The Col-0 vs. P1/HC Tu network speci cally highlighted the relationship between AGOs in PTGS and in relationship to viral resistance. Previous studies demonstrated that AGO2 and AGO3 upregulated to enhance the viral resistance (Alazem et al, 2017;Harvey et al, 2011;Zheng et al, 2019). AGO2 is a target of miR403, which is negatively regulated by AGO1 (Harvey et al, 2011), suggesting the upregulation of AGO2 in response to AGO1 degradation in P1/HC Tu plants.…”
Section: Network Of Hc-pro-mediated Ptgs Suppressionmentioning
confidence: 95%